2008
DOI: 10.1074/jbc.m709244200
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Ugt1 Locus in Mice Resembles Human Crigler-Najjar Type I Disease

Abstract: The 9 UDP-glucuronosyltranferases (UGTs) encoded by the UGT1 locus in humans are key enzymes in the metabolism of most drugs as well as endogenous substances such as bile acids, fatty acids, steroids, hormones, neurotransmitters, and bilirubin. Severe unconjugated hyperbilirubinemia in humans that suffer from Crigler-Najjar type I disease results from lesions in the UGT1A1 gene and is often fatal. To examine the physiological importance of the Ugt1 locus in mice, this locus was rendered non-functional by inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 72 publications
(54 reference statements)
1
85
1
Order By: Relevance
“…(ERK 1/2) in the human colon cancer cell line (HRT-18), and the genes linked to the cell cycle are significantly repressed while genes linked to the inhibition of cellular kinases are induced in Ugt-null mice (Ollinger et al, 2007;Nguyen et al, 2008).…”
Section: Bilirubin Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…(ERK 1/2) in the human colon cancer cell line (HRT-18), and the genes linked to the cell cycle are significantly repressed while genes linked to the inhibition of cellular kinases are induced in Ugt-null mice (Ollinger et al, 2007;Nguyen et al, 2008).…”
Section: Bilirubin Toxicitymentioning
confidence: 99%
“…Furthermore, many reports show that the cytotoxic effects of BR extend down to nucleus. Previous studies have demonstrated that BR induces DNA damage and disrupt cell growth via DNA oxidation and activation of extracellular signal-regulated kinase 1 and 2 (ERK1/2) (Ollinger et al, 2007;Nguyen et al, 2008;Deganuto et al, 2010).…”
mentioning
confidence: 99%
“…Reactions were stopped with 50 ll of methanol with 0.02% of butylated hydroxytoluene. Samples were centrifuged at 10,000 g for 10 min at 4°C, and supernatants were collected for HPLC-MS analysis (LC-MS) as described previously (Nguyen et al, 2008) and adapted to our instrumentation.…”
Section: Ugt1a1 Activity Determinationmentioning
confidence: 99%
“…Glucuronidation assay was performed as described previously (Nguyen et al, 2008) with minor modifications. Briefly, assays were performed after 1 hr of enzymatic reaction using the following conditions: 10 mM MgCl 2 · 6H 2 O, 50 mM TrisHCl (pH 7.7 at 37°C), 10 lg/ml phosphatidycholine, 15 lM bilirubin (bilirubin was previously dissolved in DMSO at a concentration of 0.33 lg/ll and diluted 1:10 in DMSO), 1 mM uridine diphosphate-glucuronic acid, and 1 lg/ll microsomal proteins (previously incubated for 1 hr at 4°C with digitonin at a concentration of 0.35 mg/ml of microsomes) (Gordon et al, 1984) in a total volume of 50 ll.…”
Section: Ugt1a1 Activity Determinationmentioning
confidence: 99%
“…Knock-out of the Ugt1 locus is a lethal mutation in Ugt1 Ϫ/Ϫ mice resulting in neonatal death from severe levels of unconjugated bilirubin (5). However, expression of the human UGT1 locus in the Ugt1-null background rescues the lethality.…”
mentioning
confidence: 99%